2012
DOI: 10.1002/ccd.22914
|View full text |Cite
|
Sign up to set email alerts
|

Direct stenting compared to balloon predilation in drug‐eluting stents

Abstract: DS with DES is commonly performed in clinical practice and results in similar long-term outcomes as predilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Although one randomized and two post‐hoc studies demonstrated improvement in outcome with direct DES, others revealed similarity between the two strategies . However, these later studies had insufficient power to draw a firm conclusion on clinical outcomes, particularly given the expected low‐to‐modest treatment effect and the low event rates of simple lesions.…”
Section: Discussionsupporting
confidence: 87%
“…Although one randomized and two post‐hoc studies demonstrated improvement in outcome with direct DES, others revealed similarity between the two strategies . However, these later studies had insufficient power to draw a firm conclusion on clinical outcomes, particularly given the expected low‐to‐modest treatment effect and the low event rates of simple lesions.…”
Section: Discussionsupporting
confidence: 87%
“…The findings from this analysis are in keeping with our data from the DEScover registry comparing DS with predilation in a contemporary population treated exclusively with DES; in that significant differences in hard clinical outcomes were not observed . The current study is additive as it provides biomarker data to allow a more accurate determination of peri‐procedural MI and expands the results to a population of patients treated with IVUS guidance.…”
supporting
confidence: 81%
“…39,40 However, other studies have shown divergent findings such as DS could possibly reduce angiographic restenosis and TVR. [41][42][43] More randomized trials comparing CS versus DS in patients with ACS having drug-eluting stents are warranted.…”
Section: Discussionmentioning
confidence: 99%